2022
DOI: 10.1021/jacsau.2c00402
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Hydrogenolysis of Polyethylene and Polypropylene into Propane over Cobalt-Based Catalysts

Abstract: The development of technologies to recycle polyethylene (PE) and polypropylene (PP), globally the two most produced polymers, is critical to increase plastic circularity. Here, we show that 5 wt % cobalt supported on ZSM-5 zeolite catalyzes the solvent-free hydrogenolysis of PE and PP into propane with weight-based selectivity in the gas phase over 80 wt % after 20 h at 523 K and 40 bar H2. This catalyst significantly reduces the formation of undesired CH4 (≤5 wt %), a product which is favored when using bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 57 publications
(77 reference statements)
3
46
0
Order By: Relevance
“…In a recent study, Zichittella et al reported that zeolite ZSM-5 alone was active for PE and PP hydrocracking at 250 °C over 20 h in 40 bar H 2 , although the addition of Co nanoparticles promoted stability and selectivity . To rule out the possibility that FAU and BEA supports alone are contributing to the high hydrocracking activity under the reaction conditions reported here, a series of control reactions were performed in the absence of ruthenium nanoparticles.…”
Section: Resultssupporting
confidence: 92%
“…In a recent study, Zichittella et al reported that zeolite ZSM-5 alone was active for PE and PP hydrocracking at 250 °C over 20 h in 40 bar H 2 , although the addition of Co nanoparticles promoted stability and selectivity . To rule out the possibility that FAU and BEA supports alone are contributing to the high hydrocracking activity under the reaction conditions reported here, a series of control reactions were performed in the absence of ruthenium nanoparticles.…”
Section: Resultssupporting
confidence: 92%
“…Besides heterogeneous Ru- and Pt- based catalysts for the hydrogenolysis of POs, other supported non-noble metal catalysts, such as Zr-, 60 Ni-, 61 Co- 62 and Nb- 63 based catalysts, have been demonstrated to be effective for the transformation of POs into valuable alkanes.…”
Section: Catalytic Hydroconversion Processes For Deconstruction Of Po...mentioning
confidence: 99%
“…The Co/HZSM-5 catalyst was reported for the solvent-free hydrogenolysis of LDPE, PP, mixtures of LDPE and PP, and postconsumer PE into propane with a selectivity of 80 wt% in the gas phase at 280 °C, 4 MPa H 2 for 20 h of reaction. 62 The ZSM-5 zeolite support was found to be an important host for the stabilization of dispersed oxidic cobalt nanoparticles, as well as preventing further reduction to the metallic state which is the site for CH 4 generation. In addition, the C 2 –C 4 hydrocarbon gas-phase selectivity can be tuned by using zeolites with different framework topologies, such as FAU, MOR and BEA.…”
Section: Catalytic Hydroconversion Processes For Deconstruction Of Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, over 85% of waste polyolefins are dumped in landfills or disposed of in environmentally harmful ways (e.g., incineration), contradicting the global sustainability efforts since polyolefin is another form of fossil energy [ 8 10 ]. The catalytic hydrogenolysis reaction has been developed to convert polyolefins into value-added liquid fuels under mild conditions efficiently [ 11 16 ]. The H 2 -rich system promotes the hydrogenation of cracked intermediate to form alkanes and suppresses the coke deposition [ 17 ].…”
Section: Introductionmentioning
confidence: 99%